Development of SYK NanoBRET cellular target engagement assays for gain–of–function variants - Capener, Jacob L.; Vasta, James D.; Katis, Vittorio L.; Michaud, Ani; Beck, Michael T.; Daglish, Sabrina C. D.; Cohen-Kedar, Sarit; Shaham Barda, Efrat; Howell, Stefanie; Dotan, Iris; Robers, Matthew B.; Axtman, Alison D.; et al. (Frontiers in Chemical Biology, 2024)
Spleen tyrosine kinase (SYK) is a non-receptor tyrosine kinase that is activated by phosphorylation events downstream of FcR, B-cell and T-cell receptors, integrins, and C-type lectin receptors. When the tandem Src homology 2 (SH2) domains of SYK bind to phosphorylated immunoreceptor tyrosine-based activation motifs (pITAMs) contained within these immunoreceptors, or when SYK is phosphorylated in interdomain regions A and B, SYK is activated. SYK gain-of-function (GoF) variants were previously identified in six patients that had higher levels of phosphorylated SYK and phosphorylated downstream proteins JNK and ERK. Furthermore, the increased SYK activation resulted in the clinical manifestation of immune dysregulation, organ inflammation, and a predisposition for lymphoma. The knowledge that the SYK GoF variants have enhanced activity was leveraged to develop a SYK NanoBRET cellular target engagement assay in intact live cells with constructs for the SYK GoF variants. Herein, we developed a potent SYK-targeted NanoBRET tracer using a SYK donated chemical probe, MRL-SYKi, that enabled a NanoBRET cellular target engagement assay for SYK GoF variants, SYK(S550Y), SYK(S550F), and SYK(P342T). We determined that ATP-competitive SYK inhibitors bind potently to these SYK variants in intact live cells. Additionally, we demonstrated that MRL-SYKi can effectively reduce the catalytic activity of SYK variants, and the phosphorylation levels of SYK(S550Y) in an epithelial cell line (SW480) stably expressing SYK(S550Y).